Uncovering biomarkers for chronic toxoplasmosis detection highlights alternative pathways shaping parasite dormancy - Marie G Robert; Christopher Swale; Belen Pachano; Léa Dépéry; Valeria Bellini; Céline Dard; Dominique Cannella; Charlotte Corrao; Lucid Belmudes; Yohann Couté; Alexandre Bougdour; Hervé Pelloux; et al. (EMBO Molecular Medicine)
Abstract Toxoplasma gondii, a neurotropic protozoan, causes toxoplasmosis, a prevalent zoonotic and food-borne infection, posing significant risks to immunocompromised individuals and congenital cases. The chronic phase, characterized by dormant, cyst-forming bradyzoites, is central to disease progression but is poorly understood due to the lack of serological tests to detect bradyzoite-specific antigens. This study identifies the bradyzoite serological marker (BSM) and cyst-associated BCLA as effective biomarkers for chronic toxoplasmosis. These markers showed high sensitivity and specificity in detecting cyst-bearing mice and had a positivity rate of 30% in humans with prior immunity. Bradyzoite serology helps to discriminate between recent and past infections, with BCLA improving the accuracy of the diagnosis of congenital infections. Mechanistic analyses show that the chromatin modifiers MORC and HDAC3 epistatically regulate BFD1, a key bradyzoite regulator. While BFD1 controls the expression of bradyzoite genes such as BCLA, a specific subset, including BSM, is regulated independently of BFD1. This multilayered regulation complicates the understanding of parasite persistence in humans, but offers promise for improved serologic diagnosis during pregnancy, but also in individuals with mental illness.